Tingkat Ketergantungan Gadget Pada Anak Usia Sekolah di Kota Bukittinggi - Febrina, Cory; Dewi, Sandra; Mariyana, Rina; Febrina, Wiwit (Universitas Fort De Kock Bukittinggi, 2021)
Background: The use of gadgets is one of the shortcuts for parents in accompanying their children as caregivers. At the age of adolescence in the pandemic era, it becomes a primary need to use gadgets in the online learning process, but the health impacts, including anemia, decreased role functions, decreased behavioral control, and sexual behavior deviations need to be a concern. Purpose:This study aims to determine the distribution of gadget addiction. Methods: This uses descriptive analytic. The research sample was teenagers who were taken by multistage random sampling and who met the inclusion criteria were 50 respondents. Data collection in this study used an instrument using the Smartphone Addiction Scale (SAS) questionnaire. Results: results showed most gadget addiction is dependence level Low (46%), the level of dependence moderate (34%), very low level of dependence (18%), high dependency level (2%). Conclusion: There is a need for holistic nursing interventions for individuals and families with gadget addiction based on the level of dependence, it takes the participation of schools and the community in providing education on the negative impact of gadget addiction. Keywords: Addiction, Gadget, Adolescents